The truth of it all - Florio, Gwen, 1955- (Crooked Lane, 2021)
When she finally gets a breakout case involving a teenage Iraqi refugee, public defender Julia Geary throws herself into the case until she starts receiving vicious threats against her family and her client is left in a coma, pitting her against the town's most powerful forces.